USING PROFILE HIDDEN MARKOV MODELS IN MULTIPLE SEQUENCE ALIGNMENT - Edi, Edi (Jurnal TIMES, 2016)
Sequence alignment is a method of arranging sequences of DNA, RNA, or protein to identify similar regions between the sequences. Profile HMM is a type of HMM that can be used to construct family structure of multiple sequence alignment so that it can be used as a database for aligning or finding other sequences in that family. Literature review used as a method in this paper. Softwares BioEdit and HMMER are introduced.